Does popularity matter in a TV song competition? Evidence from a national music contest - Oliver Budzinski; Julia Pannicke (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2017)
There is a considerable amount of literature analyzing factors of success in music contests, in particular those where the audience votes for the winner. However, one factor that is highlighted by the economic theory of stardom is generally neglected in the literature. In this paper, we tackle this research gap by focusing on a national music contest in Germany and investigating how popularity of the participating artists influences the final voting results. We employ two different concepts of popularity. First, we collected data regarding the artist's former success (MacDonald-popularity) using music charts data. Second, we proxy the media presence of the artists (Adler-popularity) using hits in traditional and new media. In our analysis, we find empirical evidence that the artist's ex-ante popularity positively affects the outcome of voting results. Interestingly, media presence matters more than former success. Furthermore, displaying the characteristics of a one-hit won-der harms success in the contest.
Keywords: L82; Z10; Z19; 330; popularity; superstar effect; biased voting; Bundesvision Song Contest; cultural economics; media economics